High‐Energy Surf Zone Currents and Headland Rips at a Geologically Constrained Mesotidal Beach. Issue 10 (20th October 2020) - Mouragues, Arthur; Bonneton, Philippe; Castelle, Bruno; Marieu, Vincent; Jak McCarroll, R.; Rodriguez‐Padilla, Isaac; Scott, Tim; Sous, Damien
Abstract: We analyze Eulerian and Lagrangian measurements of wave‐induced circulation collected during a 3‐week field experiment at a high‐energy mesotidal barred beach with the presence of a 500‐m headland and a submerged reef. Small changes in wave and tide conditions were found to largely impact circulation patterns. Three main regimes were identified depending on offshore wave obliquity: (1) Under shore‐normal configuration, the flow was dominated by cross‐shore motions, except for moderate waves at low tide, with the presence of a quasi‐steady circulation cell on the reef. (2) Under shadowed configuration, an onshore‐directed current flowing away from the headland and a weak oscillating eddy were present outside and inside the shadow region, respectively. (3) Under deflection configuration, a deflection rip flowing against the headland and extending well beyond the surf zone was present, with activity maximized around low tide for moderate waves. Under 4‐m oblique waves, the deflection rip was active regardless of the tide with mean depth‐averaged velocities up to 0.7 m/s 800‐m offshore in 12‐m depth, with energetic low‐frequency fluctuations. Our results emphasize the ability of deflection rips to transport materials far offshore, suggesting that such rips can transport sediment beyond the depth of closure. This study indicates that a wide variety of wave‐driven circulation patterns can occur and sometimes coexist on beaches with prominent geological settings. Changes in the dominant driving mechanism can occur as a result of small changes in wave and tide conditions, resulting in more spatially and temporally variable circulation than along open sandy beaches. Plain Language Summary: Most field experiments about wave‐induced circulation patterns have been conducted along open sandy beaches, while experiments in geologically constrained environments are scarce. We performed intensive field measurements at a high‐energy beach with the presence of a 500‐m headland and a submerged natural reef. Three main circulation patterns were identified depending on the offshore wave obliquity. For shore‐normal waves, cross‐shore motions dominated the nearshore region, while oblique wave configurations resulted in more complex horizontal circulation. In particular, under intense headland‐directed longshore current, the flow was deflected seaward against the headland. This deflection resulted in an intense seaward flowing jet (deflection rip) extending well beyond the surf zone edge, particularly during storm conditions. Such findings highlight the ability of these deflection rips to dominate water and sediment exchanges between the nearshore and the inner shelf region. Our study further outlines the more spatially and temporally variable circulation patterns occurring along geologically constrained beaches compared to open sandy beaches, ranging from small recirculating cells across the reef to a large deflection rip extending hundreds of meters beyond the surf zone. Key Points: In situ measurements are analyzed to identify the main circulation patterns occurring at a high‐energy geologically constrained Small changes in offshore wave height and obliquity or tide elevation were found to impact circulation patterns across the entire field This study emphasizes the ability of deflection rips to extend far offshore, particularly during very energetic oblique wave conditions